Xi`s Thriftstore Enterprise / Serhan Salim ... [et al.] - Serhan, Salim; Joseph, Kellystina; Johar, Izharul Amree; Robbie, Rachel; Md. Hasyim, Faiziantty (2012)
Administration is most important in any type of business. The administration of any business forms an important role where the business routines are maintained and controlled. It is also the body that manages the overall company’s action towards to achieved the mission and objectives The best way to ensure that the objectives achieved is by implementing the policy, procedures, determine the job description for our staff, coordinating and handling their needs which involves the salary and fringe benefits such as Employees Provident Fund (EPF), the Social Security Organization (SOCSO) and other benefits to each employee that involve in our business The name of our company is Xi’s Thrifstore Enterprise. For your information, there is a lot of shop that sell the used clothes, accessories, bags, shoes and pants but there is no shop that sells and provides the free services to their customers to help them find out which one for the one’s fashion they want. Whereby the nature of Xi’s Thrifstore Enterprise is selling clothes at lower price and also provides free services for the customers while at the same time offer them more discounts for more items bought. Meanwhile, our collections such as clothes, bags, accessories, shoes and pants will be the main product of Xi’s Thrifstore Enterprise. Our company would like to "Fulfill your needs & Serve you better”. Xi’s Thrifstore Enterprise is located at Cafe New Academic Building, UiTM Kota Kinabalu Sabah Cafe New Academic Building, UiTM Kota Kinabalu Sabah is a strategic location for Xi’s Thrifstore operates their business because it is the central place in the University, which allows all students and staffs’ UiTM easy to come. In addition, it is near with our office which is located at Indah Permai, Sepanggar. That’s the main reasons why we choose Cafe at New Academic Building because the place is so strategic and the price rentals here also is affordable.